2019
DOI: 10.1021/acsanm.9b01115
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Thick Fluorinated Ionic Liquid Films as Lubricants in Data-Storage Devices

Abstract: Media lubricants are critical to the reliability of hard disc drives (HDDs). Ideally, the lubricant should have high thermal stability and low monolayer (ML) thickness. Unfortunately, the state-of-the-art lubricant perfluoropolyether (PFPE) only has limited thermal stability, and its ML is relatively thick due to the polymeric chain structure. In this study, we showed that an ionic liquid (IL) with imidazolium cations and fluorinated anions, [Bmim]­[FAP], has higher thermal stability than PFPE Z-tetraol based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…Unlike on negatively charged mica and silica, neither aggregation nor double-layering quantized growth has been observed during the film growth processes on amorphous carbon, indicating a fairly smooth increase in the local film thicknesses. At the interface between IL and amorphous carbon, π–π + stacking interaction occurs between the delocalized π + electrons from the cation imidazolium ring and the localized π electrons from the sp 2 carbon on the amorphous carbon surface. , The random distribution of the sp 2 carbon in the amorphous carbon provides high conformational flexibility for the respective IL cations to arrange themselves and fill in vacant solid surface areas. The IL anions subsequently pack on the cation layer as a result of the electrostatic interaction between the IL ions to maintain electroneutrality .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike on negatively charged mica and silica, neither aggregation nor double-layering quantized growth has been observed during the film growth processes on amorphous carbon, indicating a fairly smooth increase in the local film thicknesses. At the interface between IL and amorphous carbon, π–π + stacking interaction occurs between the delocalized π + electrons from the cation imidazolium ring and the localized π electrons from the sp 2 carbon on the amorphous carbon surface. , The random distribution of the sp 2 carbon in the amorphous carbon provides high conformational flexibility for the respective IL cations to arrange themselves and fill in vacant solid surface areas. The IL anions subsequently pack on the cation layer as a result of the electrostatic interaction between the IL ions to maintain electroneutrality .…”
Section: Resultsmentioning
confidence: 99%
“…The IL studied was 1-butyl-3-methylimidazolium tris­(pentafluoroethyl)­trifluorophosphate ([Bmim]­[FAP], ≥ 99.0%), which contains a cation imidazolium ring and was acquired from Millipore Sigma. [Bmim]­[FAP] has exceptional hydrophobicity, and it can be readily dissolved in 2,3-dihydrodecafluoropentane (trademark as Vertrel XF by Chemours, purchased from Fisher Scientific, and used as received) to make dilute solutions . The vapor pressure of Vertrel XF is 30.1 kPa (0.297 atm) at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al used atomic force microscopy (AFM) to show that the monolayer thickness of the IL is only half of that of Z-Tetraol (MW: approximately 2000). They concluded that smaller monolayer thickness of the IL is attributed to the smaller molecular size of the material [15]. The IL in that study was general one which has an typical imidazolium cation and a fluorinated anion.…”
Section: Introductionmentioning
confidence: 74%